2020
DOI: 10.3390/medicina56010035
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Medicine in Interventional Oncology: A Virtuous Alliance

Abstract: This review aimed to identify the potential role of integrative medicine in interventional oncology. The music therapy; stress management techniques; guided imagery, including virtual reality; clinical hypnosis; and digital sedation may all be efficient on anxiety and pain during procedures performed in interventional oncology. Beyond pharmacological sedation, the implementation of integrative medicine to interventional oncology may, therefore, improve the support and care of cancer patients, which may further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Performing vertebral fixation appears not challenging and may be further implemented in routine. However, these procedures required general anesthesia [ 14 , 15 ]. The mean KAP 34.6 ± 23.1 Gy.cm 2 (20.2–42.5), mean AK 358.3 ± 240.6 mGy (218.5–422.5) and mean FT of 15.6 ± 7.9 min (11–19.8) calculated in this study were lower to the reference strandards required by the European Directive 2013/59/Euratom in interventional radiology for a vertebroplasty in 1 level (KAP: 60 Gy.cm 2 , AK: 610 mGy and FT: 9 min) or 3 or more levels (110 Gy.cm 2 , 1160 mGy and 14 min) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performing vertebral fixation appears not challenging and may be further implemented in routine. However, these procedures required general anesthesia [ 14 , 15 ]. The mean KAP 34.6 ± 23.1 Gy.cm 2 (20.2–42.5), mean AK 358.3 ± 240.6 mGy (218.5–422.5) and mean FT of 15.6 ± 7.9 min (11–19.8) calculated in this study were lower to the reference strandards required by the European Directive 2013/59/Euratom in interventional radiology for a vertebroplasty in 1 level (KAP: 60 Gy.cm 2 , AK: 610 mGy and FT: 9 min) or 3 or more levels (110 Gy.cm 2 , 1160 mGy and 14 min) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In interventional radiology, the integration of ergonomics in the workplace must balance the ergonomic disadvantages of shielding [ 11 ]. Specific recommendations for the angiographic room must now be provided to preserve the well-being of IRs [ 58 ]. Firstly, equipment dedicated to IRs is needed [ 59 ].…”
Section: Future Developmentsmentioning
confidence: 99%
“…These include music therapy, acupuncture, and massage therapy (11); reflexology and mind-body or energy therapies for oncology patients (12); craniosacral or Korean hand therapy in cardiology (13); and guided imagery, hypnosis, or acupuncture in the surgical setting (14). Other IM modalities shown to relieve stress include yoga, Qi Gong, biofeedback, meditation, and Tai Chi (15)(16)(17). Two recently published trials reported the beneficial effect of various IM therapies for HCPs working in frontline COVID settings in reducing stress levels and improving both emotional well-being and quality of sleep (18,19).…”
Section: Introductionmentioning
confidence: 99%